Predictors of early recurrence following neoadjuvant chemotherapy and surgical resection for localized pancreatic adenocarcinoma. Issue 3 (24th April 2021) - Narayanan, Sowmya; AlMasri, Samer; Zenati, Mazen; Nassour, Ibrahim; Chopra, Asmita; Rieser, Caroline; Smith, Katelyn; Oyefusi, Vivianne; Daum, Tracy; Bahary, Nathan; Bartlett, David; Lee, Kenneth; et al.
Abstract: Background and Objectives: Neoadjuvant chemotherapy (NAT) for pancreatic adenocarcinoma (PDAC) is increasingly being utilized. However, a significant number of patients will experience early recurrence, possibly negating the benefit of surgery. We aimed to identify factors implicated in early disease recurrence. Methods: A retrospective review of pancreaticoduodenectomies performed between 2005 and 2017 at our institution for PDAC following NAT was performed. A 6‐month cut‐off was used to stratify patients into early/late recurrence groups. Multivariate analysis was performed to identify predictors of recurrence. Results: Of 273 patients, 64 (23%) developed early recurrence or died within 90 days of surgery. The median time to recurrence was 4 months (95% confidence interval [CI]: 2.2–4.3) in the early group versus 16 months (95% CI: 13.7–19.9) in the late group. The former had higher baseline and post‐NAT Ca19‐9 levels than the latter (472 vs. 153 IU/ml, p = 0.001 and 71 vs. 39 IU/ml, p = 0.005, respectively). A higher positive lymph node ratio significantly increased the risk of early recurrence (hazard ratio [HR]: 15.9, p < 0.001) while adjuvant chemotherapy was protective (HR: 0.4, p < 0.001). Conclusion: Our findings acknowledge the limitations of clinically measured factors used to ascertain response to NAT and underline the need for individualized molecular markers that take into consideration the specific tumor biology.